When does near-wall hindered diffusion influence mass transport towards targets? - Eloul, S; Kätelhön, E; Compton, R (Royal Society of Chemistry, 2016)
The diffusion of a particle is slowed as it moves close to a surface. We identify the conditions under which this hindered diffusion is significant and show that is strongly dependant on the sizes of both the particle and the target. We focus particularly on the transport of nano-particles to a variety of targets including a planar surface, a sphere, a disc and a wire, and provide data which allows the frequency of impacts to be inferred for a variety of experimental conditions. Equations are given to estimate the particle fluxes and we explain literature observations reported on the detected frequency of impacts. Finally we observe a drastic effect on the calculation of the mean first passage time of a single particle impacting a sub-micron sized target, showing the importance of this effect in biological systems.